PERAMALAN EKSPOR TIGA KOMODITAS UTAMA SEKTOR PERIKANAN MENGGUNAKAN METODE TIME SERIES: ARIMA - Nabillah, Faradiba; Munir, Zainul; Permatasari, Ririt Dwiputri; Anggraeni, Andini Setyo; Safitriyana, Safitriyana (LPPM Universitas Bina Bangsa, 2024)
Batam City is one of the cities in Indonesia which is located in a strategic area on international shipping routes and has a sea area of 3,675 km so it has great potential for exporting fishery products, based on main commodities. Based on data from the Ministry of Maritime Affairs and Fisheries (KKP) in 2022, the performance of the export value of Indonesian fishery products during 2022 experienced positive growth of 21.63 percent compared to 2021. In 2021, the export value of Indonesian fishery products reached 1,258 million USD, increasing to 1,530 million USD in 2022. This fact shows that the marine fisheries sector still offers significant opportunities today. However, there are several obstacles that stand in the way of the export process. These obstacles include the low level of technology application, unequal infrastructure development in various fisheries centers, limitations in providing capital, low utilization of Indonesia's marine potential, and the use of fishing systems in the production process which are deemed unable to utilize Indonesia's marine potential optimally. Given this problem, it is interesting to see the forecast for fishery product exports according to the main commodities in the city of Batam. Is there an increase or a decrease? So the aim of this research is to describe the predicted results of the export value of fishery products according to 3 main commodities, namely shellfish, crab and shrimp in Batam City in the next 5 years. This research method is quantitative using the time series method: ARIMA. The research results show that the estimated export of shellfish and crab will decrease from 2023 - 2027. Meanwhile, the estimated export of shrimp will increase from 2023 - 2027